ASPECTS OF STRATEGIC POLICY OF FINANCIAL RECONSTRUCTION OF THE ENTERPRISE - KHOMA, Dmytro; LOPATOVSKYI, Victor; SHPYLOVYI, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The research emphasizes the relevance of the problem of strategic management in the field of financial rehabilitation of the enterprise. The purpose of the study is the further development of the theoretical-methodical and methodical-applied principles of strategizing the policy of financial rehabilitation of enterprises. It is shown that the dynamism of the external and internal environment of enterprises, the emergence of new systemic and critically complicated threats, such as war and its negative consequences, determine the need for further development of methodological and applied foundations of strategizing the policy of financial rehabilitation of business entities. The principles of the formation of information and analytical support of the management subsystem of the financial rehabilitation of the enterprise are summarized. The position of strategic analysis of financial security in the system of financial rehabilitation of the enterprise is defined. The classical procedure of SWOT analysis with assessment of the company’s strengths and weaknesses in relation to its opportunities and threats from the external environment based on PEST analysis is characterized. The advantages and disadvantages of strategic planning of the financial rehabilitation of a business entity are determined. The principles of budgeting, auditing and control of the process of financial rehabilitation of the enterprise are defined. The scientific novelty of the research results lies in the further development of strategic management in the field of financial rehabilitation, ensuring the improvement of the financial condition and strengthening the financial security of economic entities. The applied value of the research results consists in determining the elements of the management mechanism of the financial rehabilitation of the enterprise, in particular, financial interests, functions, principles and methods of management, organizational structure, management personnel, management techniques and technologies, financial instruments, criteria for assessing the financial condition. In this sense, the mechanism for ensuring the financial rehabilitation of the enterprise represents the unity of the management process and the management system.